Five year trend of aerobic bacteria isolated from patients with neonatal sepsis in a tertiary care centre, North Kerala, India - Jakribettu, Ramakrishna Pai; A., Bindu; V., Twinkle; Neliyathodi, Fysal (International Journal of Contemporary Pediatrics, 2020)
Background: Antimicrobial resistance has reached to a significant proportion globally. This antimicrobial resistance increases the cost of health care in addition to the existing burden of the prevalence of infectious disease in developing countries. We need to have institutional protocols based on the standard guidelines. It is important for the clinician to use antibiotics only when it is necessary. Thus, the present study was undertaken to know the bacteriological profile and antibiogram of aerobic pathogens isolated from blood samples of patients in NICU during 2012 -2016. Methods: This retrospective study was conducted at Clinical Microbiology and Paediatric department, MES Medical College, Perinthalmanna, between January 2012 to December 2016. All blood samples from suspected Neonatal sepsis were included in the study. The positive samples were cultured as per standard microbiological procedure and antimicrobial susceptibility was done as per CLSI guidelines. Results: During the study period of 5 years, out of 2022 blood samples received from NICU 251 (12.41%) were positive. During the study period, male patients (146, 58.17%) were more than the female. The Gram-positive isolates accounted for 135 (53.78%) isolates compared to Gram negative isolates 115 (45.81%). Authors had a single isolate of Candida species in 2014. Among the Gram positive isolates, Staphylococcus aureus (77/135) was the commonest and Klebsiella pneumoniae (51/115) among the Gram negative isolates. There was a steady rise in MRSA isolation rate in five years. The commonly used antibiotic in neonatal sepsis i.e., Ampicillin and Gentamicin, was observed to have high level of resistance. No resistance was observed against Vancomycin, Teicoplanin, Linezolid among Gram positive and against Carbapenems among Gram negative pathogens. Conclusions: As Gram positive organisms were the most common pathogen isolated in patients with neonatal septicaemia in our study population. The Staphylococcus aureus and Klebsiella pneumoniae were the common isolates. Following this study, Piperacillin tazobactum is considered as the drug for empirical therapy. Vancomycin and carbapenems are considered as reserve drug and escalated only following the report from microbiology report.